Hip fractures and area level socioeconomic conditions: a population-based study - Rapp Kilian; Becker Clemens; Wildner Manfred; Haastert Burkhard; Icks Andrea; Dragano Nico; Meyer Gabriele; Rosenbauer Joachim (BMC, 2009)
Abstract Background Only a limited number of studies have analyzed the association between hip fracture incidence and socioeconomic conditions. Most, but not all found an association, and results are in part conflicting. The aim of our study was to evaluate the association between hip fractures and socioeconomic conditions in Germany, from 1995 to 2004, on a census tract area level. Methods We used data from the national hospital discharge diagnosis register and data on socioeconomic and demographic characteristics of 131 census tracts from official statistics. Associations between the hip fracture incidence and socioeconomic conditions were analyzed by multiple Poisson regression models, taking overdispersion into account. Results The risk of hip fracture decreased by 4% with a 7% increase (about one interquartile range) of non-German nationals. It decreased by 10% with a 6% increased rate of unemployment, increased by 7% with a 2% increase of the proportion of welfare recipients, and also increased by 3% with an increase of the proportion of single parent families of 1.9%. Conclusion Our results showed weak associations between indicators of socioeconomic conditions at area level and hip fracture risk; the varied by type of indicator. We conclude that hip fracture incidence might be influenced by the socioeconomic context of a region, but further analysis using more specific markers for deprivation on a smaller scale and individual-level data are needed.